(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
The aim of this research is to find out why the ability of teaching staff to improve the quality of cadets’ educational outcomes at the Magelang Military Academy is still not optimal, to formulate the efforts made to improve the abilities of teaching staff to improve the quality of cadets’ educational outcomes at the Magelang Military Academy. The results of the research show that the reason why the ability of teaching staff to improve the quality of cadet student outcomes at the Magelang Military Academy is still not optimal is due to, among other things, the lack of basic skills possessed by Gadik in managing learning principles, Gadik’s role is less than optimal in providing understanding to students regarding knowledge. (Knowledge) and experience to eliminate mis-understanding, attitude aspects still need to be improved in accordance with applicable norms. Efforts made to improve the ability of teaching staff to improve the quality of cadet student outcomes at the Magelang Military Academy are by improving the Skills of Akmil Girls Magelang is in accordance with improving or upgrading Gadik’s skills which is carried out at least once a semester to ensure the depth and breadth of learning material, guaranteeing the distribution of learning material in accordance with the KKNI, the Magelang Akmil curriculum, improving or upgrading Gadik’s skills in preparing learning plans, implementing learning plans, carrying out evaluations during the PBM, as well as following up on the evaluation results, increasing the knowledge of the Magelang Military Academy Education Staff who are required to have academic qualifications and educational competencies, with the lowest level of education (S1, Masters, Doctoral) which must be met, improving attitudes (Attitude) Magelang Military Academy educational staff in carrying out coaching or upgrading as well as psychological tests to improve Gadik’s personality which is steady and stable, mature, dignified, wise and has noble morals and can be a role model, coupled with Spiritual Guidance (Binroh) activities.